Development of a Student Worksheet Based on Project-Based Learning to Improve Learning Outcomes of Junior High School Students - Rahmah, Yuniarti Khairini; Hafizah, Ellyna; Annur, Syubhan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This research involves the development of a Student Worksheet based on project-based learning for the solar system sub-material, focusing on improving the learning outcomes of junior high school students. The purpose of this study is to identify the level of validity, practicality, and effectiveness of the project-based learning Student Worksheet. The method employed in this research is Research and Development (R&D), utilising the ADDIE approach as the development model. This study demonstrates that project-based learning, specifically the Student Worksheet on solar system sub-materials, is deemed highly valid, with a validity value of 0.88, aimed at enhancing student learning outcomes. The practicality of the results from a student response questionnaire, with 82.24% of students agreeing, indicates that the Student Worksheet is highly practical. Effectiveness based on knowledge learning outcomes, with the calculation of n-gain from pretest and posttest, obtained an average n-gain of 0.71 with high criteria, attitude learning outcomes obtained an average of 90.67% which is categorised as very good, and learning outcomes skills obtained an average of 91% which is categorized as very good. The results of the study demonstrate that the Student Worksheet project-based learning on the solar system sub-material is feasible for use, as it meets the criteria of validity, practicality, and effectiveness in improving student learning outcomes. The implications of this research suggest that project-based learning Student worksheets can serve as an alternative, innovative teaching material that encourages active student involvement, improves critical thinking skills, and provides educators with a reference for developing learning tools that align with the demands of the Independent Curriculum and 21st-century learning.